A strongly ill-posed integro-differential parabolic problem with integral boundary conditions - Lorenzi, Alfredo (Mathematical Modelling and Analysis, 2013)
Via Carleman estimates we prove uniqueness and continuous dependence results for an identification and strongly ill-posed linear integro-differential parabolic problem with the Dirichlet boundary condition, but with no initial condition. The additional information consists in a boundary linear integral condition involving the normal derivative of the temperature on the whole of the lateral boundary of the space-time domain.